Joint Injection or Aspiration before Total Knee Arthroplasty: Does It Increase the Risk of Periprosthetic Joint Infection? - Nin, Darren Z.; Chen, Ya-Wen; Talmo, Carl T.; Hollenbeck, Brian L.; Mattingly, David; Zvi, Yoav; Niu, Ruijia; Chang, David C.; Smith, Eric L. (The Journal of Knee Surgery, 2024)
Injections are a common preoperative treatment for patients who eventually undergo total knee arthroplasty (TKA). However, recent studies have shown a relationship between preoperative injections and adverse outcomes following surgery. The purpose of this study was to characterize the type of intra-articular procedure patients receive in the acute period prior to surgery and determine their association with postoperative periprosthetic joint infection (PJI).An observational cohort study was conducted using the Merative MarketScan databases. Patients who underwent primary TKA between April 1, 2019, and July 4, 2021, were included in the study. Patients were grouped according to the type of intra-articular procedure they received within the 90-day period prior to TKA: (i) intra-articular hyaluronic acid (IA-HA), (ii) intra-articular corticosteroid (IA-CS), (iii) aspiration, and (iv) no drug injections or aspirations. The primary outcome was the postoperative 180-day PJI rate.A total of 43,219 patients were included in the study. About 11.8% of patients were found to have received at least one injection or aspiration in the 90 days prior to their TKA. The most common injection performed was IA-CS (78.3%), followed by aspiration (13.0%) and IA-HA (8.7%). No image guidance was performed for 92.3% of injections, with most being administered between 61 and 90 days before surgery (93.6%). Rates of PJI at 180 days were similar between patients with and without injections (OR = 1.11, p = 0.569). Neither drug type nor image guidance had an effect on the overall postoperative PJI rate.Injections performed prior to TKA do not increase the risk of developing postoperative PJI.
Keywords: intra-articular injections; total knee arthroplasty; outcomes; infection